PENGARUH MOTIVASI KERJA DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU SMK NEGERI SE-KECAMATAN RAMBAH KABUPATEN ROKAN HULU - YULIA SARI; MAKHDALENA MAKHDALENA; FAKHRI RAS (Universitas Riau, 2017)
The purpose of this study was to determine the effect of motivation andinterpersonal communication either simultaneously or partially on teacher performance at statesenior vocational schools (SMKN) in Rambah district of Rokan Hulu.The study population isSMKN teachers in Rambah district Rokan Hulu 139 pearsons, with a sample of 103 pearsonsusing the formula of Taro Yamane. Form data in this study are primary data. Data werecollected by questionnaire using Likert scaleMethods of data analysis in this study multipleregression with SPSS.Research results showedthat workmotivation and interpersonalcommunication positive and significant effect to the performance of teachers eithersimultaneouslyor partially.